(untitled) - Klaus Winter (New York, 1996)
The book begins with summary of the basic priciples of CAM to lay the foundations for three major sections that cover the different areas of current research: Part A deals with the biochemistry of the CAM cycle; Part B focuses on the environmental and developmental control of CAM and underlying molecular mechanisms; Part C is devoted to the ecological diversity and evolutionary origins of CAM
Keywords: crassulacean acid metabolism - congresses